Evaluation of COVID-19 vaccination status and immune response among staff at Shahid Motahari Hospital, Urmia, 2021 - Maryam Taavon; Vahid Tanhaei Marand; Sadegh Feizollahzadeh (Health Science Monitor)
Background & Aims:  The Ministry of Health and Treatment implemented vaccination as one of the primary strategies to control the coronavirus disease 2019 (COVID-19) pandemic. Given their critical role in treatment and disease control, healthcare workers were prioritized for vaccination. This study aims to assess the vaccination status and level of immunity against COVID-19 among healthcare workers at Shahid Motahari Hospital in Urmia, Iran, in 2021. Materials & Methods:  A cross-sectional study was conducted with 150 volunteer healthcare workers at Shahid Motahari Hospital. Venous blood samples were collected to measure severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) neutralizing antibodies using the ELISA method. Data analysis was performed using version 16 of SPSS software. Results: The participants had a mean age of 37.5 years, with 47.3% being male. A significant 98% of the participants were vaccinated against COVID-19. The predominant vaccines administered were Sputnik V (72%), AstraZeneca (54%), and Sinopharm (27%). The mean level of SARS-CoV-2 neutralizing antibodies was significantly higher in vaccinated individuals compared to unvaccinated individuals (p = 0.001). There was no significant difference in antibody levels between male and female participants (p = 0.67). A positive correlation was observed between the number of vaccine doses received and the level of neutralizing antibodies (R = 0.207). Conclusion: Vaccination with the mentioned vaccines, whether administered singly or in combination, effectively increased serum antibody levels, providing sufficient protection against COVID-19 for healthcare workers. To maintain immunity levels among healthcare workers and protect against emerging strains of the virus, it is essential to administer booster doses.